Association of LEPR Gln223Arg polymorphism with T2DM: A meta-analysis. Issue 3 (September 2015) - Liu, Ying; Chen, Shu-Qin; Jing, Zhao-Hai; Hou, Xu; Chen, Ying; Song, Xue-Jia; Lv, Wen-Shan; Wang, Robin; Wang, Yan-Gang
Highlights Several polymorphisms of LEPR gene have been found in populations exhibiting different morbidity of diabetes. A meta-analysis was conducted to evaluate the association of LEPR Gln223Arg polymorphism with type 2diabetes (T2DM). Sixteen individual studies with 7827 subjects were included into the meta-analysis, with six studies performed in Caucasian countries, the other ten studies performed in Asian. Current studies suggest that LEPR Gln223Arg polymorphism may not affect the susceptibility with type 2diabetes (T2DM).